Severe pre-eclampsia in the gynecology and obstetrics department of the CHR of Koudougou: epidemiological, clinical, therapeutic and prognostic aspects - Djiguemde, Nebnomyidboumbou Norbert Wenceslas; Lankoande, Martin; Pitroipa, Samira L.; Ouedraogo, Estelle; Dabire, N. S. Madeleine; Bonane, Blandine Thieba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To study the epidemiological, clinical, therapeutic and prognostic aspects of severe pre-eclampsia in the gynecology and obstetrics department of the CHR of Koudougou. Methods: descriptive cross-sectional study with prospective collection from January 1 to December 31, 2018. The variables studied focused on clinical socio-demographic characteristics, treatment and prognosis. The women admitted to the department and meeting the criteria for severe pre-eclampsia were included, more than 20 weeks of amenorrhea with an increase in blood pressure, presence of albumin in the urine and signs of clinical or biological seriousness. Results: Severe pre-eclampsia represented 2.3% of admissions and 3% of deliveries. The clinical profile was that of a young housewife (51.2%), married (72.4%), nulliparous (44.1%) with a pregnancy in the 3rd trimester. Symptoms were dominated by headache (53.5%) and diastolic blood pressure ≥110 mmHg (66.9%), with albuminuria greater than two crosses and hyperuricemia. Magnesium sulfate and clonidine were the most commonly prescribed anticonvulsant and antihypertensive drug, respectively. Cesarean section was performed in 53% of cases. Maternal complications were noted in 57.5% of cases without death. However, the fetus took a heavy toll with 50.7% morbidity and 14% perinatal mortality. Conclusions: Severe pre-eclampsia is responsible for heavy morbidity - perinatal mortality. Improving maternal and fetal prognosis will require compliance with treatment protocols and greater accessibility of care at all levels of the health pyramid.